IMPACTS OF THE FAILURE OF SELECTED TRANSPORT INFRASTRUCTURE ELEMENTS (Perner's Contacts, 2012)
History provides many cases in which the failure of transport of food and other materials led to great loss of lives and turnovers in wars. Therefore, the transport infrastructure is one of the main infrastructures that create a critical infrastructure in the area. The object of monitoring are thus not only the immediate impacts of selected critical components, but the whole cascade of potential impacts at selected time intervals during the loss of functionality of transport system; the whole supply chain is influenced at failures of critical items. The research objective is to monitor and subsequently evaluate the severity of the consequences of failure of two selected elements of transport infrastructure. These are studied impacts on public assets in two cases of failure: the critical section of the busiest highway; and bus station in the centre of a large city.